If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 5 = x + 7 Reorder the terms: 5 + 2x = x + 7 Reorder the terms: 5 + 2x = 7 + x Solving 5 + 2x = 7 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 5 + 2x + -1x = 7 + x + -1x Combine like terms: 2x + -1x = 1x 5 + 1x = 7 + x + -1x Combine like terms: x + -1x = 0 5 + 1x = 7 + 0 5 + 1x = 7 Add '-5' to each side of the equation. 5 + -5 + 1x = 7 + -5 Combine like terms: 5 + -5 = 0 0 + 1x = 7 + -5 1x = 7 + -5 Combine like terms: 7 + -5 = 2 1x = 2 Divide each side by '1'. x = 2 Simplifying x = 2
| y=(x+1)2 | | 77=10x-53 | | 6x+9=8x-13 | | 3(x+3)=2(x+5) | | 7x+5(-4-13)=-169 | | 4x+50=8x-10 | | -9=-4+x/13 | | 83-3x=15x+21 | | 4w+2=18 | | 14-8x=89-29x | | -6x+6(-2x-12)=144 | | 2a^2+18a+28= | | 9x(2x+7)= | | 2345x-678=678 | | 5(3-2x)=75 | | 2x^2+13x=24 | | -496=-8(-10x-8) | | -165=5(5x-3) | | 5x+1=7+3x | | 160=-7x-6(2x+5) | | 4(5x+7)+-8=-16 | | 3(x-1)=3x+2 | | 8x+8=8x+12 | | 4r+15=4r+11 | | 4xy*6xy= | | -2(4x+5)-11=-5 | | 2x-2=x+x | | 23x-8-14x=10 | | 2(b+8)-9=9 | | 2x^2=-144 | | 3k^2-11k-20=0 | | (8x^3)(2)= |